2022
DOI: 10.1007/s00259-022-05981-9
|View full text |Cite
|
Sign up to set email alerts
|

The potential of a medium-cost long axial FOV PET system for nuclear medicine departments

Abstract: Purpose Total body positron emission tomography (TB-PET) has recently been introduced in nuclear medicine departments. There is a large interest in these systems, but for many centers, the high acquisition cost makes it very difficult to justify their current operational budget. Here, we propose medium-cost long axial FOV scanners as an alternative. Methods Several medium-cost long axial FOV designs are described with their advantages and drawbacks. We describe their potential for higher throughput, more cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In figure 9 we summarize relative sensitivity and costs for fixed AFOV scanner designs: a standard PET scanner design that uses 20 mm thick LSO crystals, a standard PET scanner with axial gaps corresponding to 40% of the active ring width, a PET scanner using 10 mm thick LSO crystals, and a PET scanner using 20 mm thick BGO crystals. Developing scanners with gaps (or more generally, incomplete detector coverage) is one way to reduce cost of long AFOV PET systems (Vandenberghe et al 2023). For the calculations, the scanner with axial gaps is modelled on the PPEx scanner where initial DAQ limitations restricted full scanner ring readout, but did not have an impact on image quality or quantitative accuracy beyond that of reduced intrinsic sensitivity (50%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In figure 9 we summarize relative sensitivity and costs for fixed AFOV scanner designs: a standard PET scanner design that uses 20 mm thick LSO crystals, a standard PET scanner with axial gaps corresponding to 40% of the active ring width, a PET scanner using 10 mm thick LSO crystals, and a PET scanner using 20 mm thick BGO crystals. Developing scanners with gaps (or more generally, incomplete detector coverage) is one way to reduce cost of long AFOV PET systems (Vandenberghe et al 2023). For the calculations, the scanner with axial gaps is modelled on the PPEx scanner where initial DAQ limitations restricted full scanner ring readout, but did not have an impact on image quality or quantitative accuracy beyond that of reduced intrinsic sensitivity (50%).…”
Section: Discussionmentioning
confidence: 99%
“…While studies have shown significant performance gains with these systems, cost remains prohibitive for most clinical and research sites. Hence, there is potential to develop new long AFOV systems that provide all the advantages of TB-PET imaging at a reasonable cost (Vandenberghe 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Towards a longer, less costly AFOV scanning geometry Due to the high cost of more extended AFOV PET systems, various design solutions have been proposed to benefit from most of the advantages of total body PET (TB-PET) while reducing the total manufacturing cost. These different designs are discussed in this article [188]. The first optimal solution that can be adopted is to build a scanner with an average axial FOV of around 60 to 70 cm in length, which is the average distance between the brain and heart of a human or the total length of the torso.…”
Section: Scanner Diametermentioning
confidence: 99%
“…The question is whether the revived tracers are good enough to justify these extra costs and whether patients and healthcare insurances are willing to pay for this. The development of inexpensive extended FOV PET with new lower cost elements may have a critical role in the coming years [34].…”
Section: High Costs Of An Extended Fov Cameramentioning
confidence: 99%